[OP.2C: 05] ATRIAL FIBRILLATION IN HYPERTENSIVE PATIENTS. A SINGLE PILOT ANTICOAGULATION RISK MANAGEMENT CENTER. (September 2016) - Varga, A.; Tatar, C.M.; Mitre, A.; Podoleanu, C.; Tilea, I.
Abstract : Objective: Atrial fibrillation is one of the most frequent complications of hypertension. Proper management of this condition with anticoagulation treatment requires data of the atrial fibrillation events rate in hypertensive population. Adequate standards of safety and optimal level of anticoagulation for preventing further cerebrovascular events is the target of this pilot center. Design and method: Medical records from a family medicine database practice were evaluated. 525 hypertensive patients, mean age 62.06 ± 12.303 years, were followed for a period of 4 years in order to investigate the prevalence of cardiovascular events, with primary endpoint atrial fibrillation and secondary endpoint hospitalization. Adherence to antihypertensive treatment was also evaluated. Results: Atrial fibrillation as a primary endpoint was reported in 54 (10.46%) hypertensive active patients (516). Myocardial infarction was reported in 18 (3.48%) hypertensive patients; stroke was reported in 33 (6.39%) hypertensive patients. The secondary endpoint of the study was the number of hospitalization; 49 cases were admitted to cardiology units; 21 cases were admitted to neurology and 17 cases were admitted to internal medicine, with a positive correlation for cardiology admission, p < 0.0001. We did not demonstrate a positive association between the non-adherence to antihypertensive treatment and atrial fibrillation (paroxysmal, persistent or permanent) (p = 0.17) or non-fatal MI events (p = 0.57), stroke (p = 0.82). At a high level (80%) of adherence to antihypertensive treatment, 15.00% of these patients presented atrial fibrillation (primary endpoint) during the over the course of four years. Over the course of the follow-up period, cardiovascular death was reported in 31 (5.60%) hypertensive patients. Conclusions: In our study, atrial fibrillation was the most prevalent complication of hypertension in a large hypertensive primary care database followed for four years. In primary care, an intensive program for the identification and assessment of the risk management of the anticoagulation therapy is needed.